2021
DOI: 10.3390/ani11061607
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Measurement of Piglet Activity Using Passive Infrared Detectors

Abstract: Measuring animal activity is useful for monitoring animal welfare in real time. In this regard, passive infrared detectors have been used in recent years to quantify piglet activity because of their robustness and ease of use. This study was conducted on a commercial farm in Northwest Spain during six complete breeding cycles. The hourly average activity of weaned piglets with a body mass of 6–20 kg was recorded and further analyzed by using a multiplicative decomposition of the series followed by a wavelet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Thus, cosine models can be a useful tool to study and predict these variables. Whereas other authors presented models with up to four daily peaks [13], in this research, animal behaviour shows a pattern with two daily peaks [8,12,14,15], coinciding with human activity inside the building, with a preference for inactivity when there is less light [2,55] and around midday [12,14]. These two peaks occur after the distribution of feed (08:00 h, 12:00 h and 16:00 h), which may be the cause for such peaks, in agreement with the evolution of the third harmonic.…”
Section: Cosine Modelsmentioning
confidence: 59%
See 3 more Smart Citations
“…Thus, cosine models can be a useful tool to study and predict these variables. Whereas other authors presented models with up to four daily peaks [13], in this research, animal behaviour shows a pattern with two daily peaks [8,12,14,15], coinciding with human activity inside the building, with a preference for inactivity when there is less light [2,55] and around midday [12,14]. These two peaks occur after the distribution of feed (08:00 h, 12:00 h and 16:00 h), which may be the cause for such peaks, in agreement with the evolution of the third harmonic.…”
Section: Cosine Modelsmentioning
confidence: 59%
“…In fact, there are substantial differences in the amount of activity of pigs between daytime and night-time, and their patterns of activity show variations depending on the time of day and the stage of growth [13]. Daily activity generally fits models with two peaks [8,12,14,15], although single-peak models have also been found during the first weeks postweaning [14] or in buildings with natural ventilation [12]. In other studies, daily activity has shown four daily peaks [13].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In recent years, the use of intelligent sensing devices for data collection has emerged as a promising solution to mitigate the problems associated with manual data collection. For instance, deploying devices like infrared sensors [18][19][20], 3D point cloud cameras [21,22], and RGB cameras [23,24] in farming or animal research settings facilitates the capture of livestock images and 3D coordinate points on their surfaces. Subsequently, employing 3D reconstruction techniques generates complete 3D models of livestock.…”
Section: Introductionmentioning
confidence: 99%